GAYA BELAJAR SISWA TUNANETRA DALAM PEMBELAJARAN PAI DI SEKOLAH UMUM (Studi Kasus SMA Taman Siswa Bekasi) - Windy Khasanah; Irham - (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2020)
This study aims to describe the learning styles used by blind students in PAI learning in publicschools. Then this study describes the supporting and inhibiting factors of blind students in studyingPAI and the quality of understanding of blind students in public schools. The school chosen was SMATamansiswa Bekasi. This type of research is a descriptive qualitative research using a case studyapproach or method, where this method describes and describes the problem in detail and depth. Datawas collected by conducting observations, interviews and documentation data at SMA TamansiswaBekasi. The results showed that the learning styles of blind students in PAI learning tended to usekinesthetic and auditory learning styles, this can be seen from the characteristics or responses thatemerged from blind students for the interactions that occurred. Awareness of the importance ofstudying PAI is the main factor that supports blind students to continue learning, then other supportingfactors emerge from their families and learning environment. In addition, there are also factors thathinder blind students, especially in learning PAI, including the absence of special education teachers,namely teachers who are competent in handling children with special needs, then the learning mediain schools is not adequate for children with special needs, especially the blind, and in terms of learningtime, PAI is felt still less effective.